2020
DOI: 10.1111/codi.15284
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the mesentery: Part III. Unusual anatomy of ileocolic vessels

Abstract: Aim The ileocolic vessels are important landmarks in advanced surgery of the midgut. The aim of the present study is to present variations of ileocolic vessels relevant to complete mesocolic excision with D3 lymphadenectomy of the right colon, within their detailed and precise morphometric framework and deriving from a large and consistent series of operated patients. Methods An ongoing prospective trial 'Safe Radical D3 Right Hemicolectomy for Cancer through Preoperative Biphasic Multidetector Computed Tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…Our Right Colon Cancer (RCC) study group has accomplished 650 colectomies of the right colon for cancer to this date, with extended mesenterectomy and D3 lymphadenectomy. We regularly perform a minute manual segmentation with 3D reconstruction on preoperative MultiDetector Computed Tomography Angiography (MDCTA) ( 2 - 4 ), which serves as a powerful tool for road-mapping and surgical planning, particularly when the complex, rare and unexpected anatomical variations may occur ( 2 , 4 ). In one of our cases ( 2 ), we found a similar ( Figure 1 ), but not identical case as reported by Du et al We found that the ileocolic artery was very short and promptly divided to the left of the superior mesenteric vein.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our Right Colon Cancer (RCC) study group has accomplished 650 colectomies of the right colon for cancer to this date, with extended mesenterectomy and D3 lymphadenectomy. We regularly perform a minute manual segmentation with 3D reconstruction on preoperative MultiDetector Computed Tomography Angiography (MDCTA) ( 2 - 4 ), which serves as a powerful tool for road-mapping and surgical planning, particularly when the complex, rare and unexpected anatomical variations may occur ( 2 , 4 ). In one of our cases ( 2 ), we found a similar ( Figure 1 ), but not identical case as reported by Du et al We found that the ileocolic artery was very short and promptly divided to the left of the superior mesenteric vein.…”
mentioning
confidence: 99%
“…We regularly perform a minute manual segmentation with 3D reconstruction on preoperative MultiDetector Computed Tomography Angiography (MDCTA) ( 2 - 4 ), which serves as a powerful tool for road-mapping and surgical planning, particularly when the complex, rare and unexpected anatomical variations may occur ( 2 , 4 ). In one of our cases ( 2 ), we found a similar ( Figure 1 ), but not identical case as reported by Du et al We found that the ileocolic artery was very short and promptly divided to the left of the superior mesenteric vein. Further, a preoperative MDCTA segmentation offers the possibility of 3D printing ( 3 ), which adds to the practical anatomical orientation before and even during operation.…”
mentioning
confidence: 99%
See 1 more Smart Citation